Distribution patters of hydrocarbon reserves in the Illizi oil and gas basin - D. V. Arcybasova; V. A. Schevyakov (Известия высших учебных заведений: Геология и разведка)
Background. The Illizi oil and gas basin is a key oil and gas region of Algeria. Although large oil and gas fields have been discovered in this region, its potential resources remain to be exhausted. According to the estimates of Zarubezhgeologiya JSC, the forecast oil and gas resources in Algeria as a whole, including the Illizi basin, amount to 837.8 million and 1,470.3 billion tons, respectively3. In order to determine directions for further geological exploration of oil and gas resources, their distribution patterns in the lithosphere should be elucidated. Aim. To determine distribution patterns and formation conditions of oil and gas deposits in Illizi basin by carrying out a statistical analysis of distribution of recoverable hydrocarbon reserves (HC) by deposits, regional oil and gas complexes, and occurrence depths. Materials and methods. The statistical distribution of hydrocarbon reserves was conducted using the data of the Information Handling Services (IHS, 2017) electronic database for the global oil and gas industry. Additional data on the geological structure and hydrocarbon potential of the Illizi basin were taken from literature sources. Results. The Illizi basin demonstrates a significant unevenness in the distribution of recoverable HC reserves. Here, the unique Tin Fuye-Tabancourt deposit and seven large deposits contain 75% of all recoverable HC reserves. The main source of HC deposits are the oil and gas mother rocks of the Silurian Tanezzuft formations, with about 60% of all recoverable HC reserves being concentrated in their immediate vicinity. The greatest concentration of HC reserves is observed in the depth range of 1–2 km (72% of the total recoverable HC reserves in the Illizi basin). The data on the accumulation depth of the main oil and gas areas and the current knowledge of the depth of oil and gas    generation indicates significant erosion processes in the post-Paleozoic. Conclusion. The revealed distribution patterns of recoverable HC reserves in the Illizi basin allowed the authors to draw conclusions about the formation conditions of oil and gas fields.